Quality Evaluation of Yoghurt Supplemented with Carrot Juice- - Sulieman,, Abdel Moneim E.; Abdelrahman, , Mushiera M.; Elkhalifa, Elamin A. (Gezira Journal of Engineering and Applied Sciences, 2018)
In the present study, carrot juice was used in the preparation of yoghurt using cow's milk. The effect of refrigerated storage (6°C) in the chemical and microbiological characteristics of yoghurt samples was investigated during 1, 7 and 15 days of storage. The chemical analyses showed that the moisture content was 88 ± 0.4% in control yoghurt in day 1 which was lower than those of carrot yoghurt samples which ranged between 89 ± 0.5% and 93 ± 0.6%. The protein content of control yoghurt (A), yoghurt supplemented with 5% carrot juice (B 1 ), yoghurt supplemented with 10% carrot juice (B 2 ) and yoghurt supplemented with 15% carrot juice (B 3 ) was 4 ± 0.06%, 3.9 ± 0.02%, 3.9 ± 0.01% and 3.8 ± 0.02%, respectively. The ash content of carrot yoghurt samples ranged between 0.45 ± 0.004% and 0.6 ± 0.07%. The total solids content was 12 ± 0.7% in control yoghurt at day 1 which was higher than those of carrot yoghurt samples (11 ± 0.3% and 7 ± 0.6%). However, the total solids content of carrot yoghurt decreased during storage.  The acidity (expressed as lactic acid %) increased progressively during storage of all yoghurt samples while the pH decreased. The microbiological analyses revealed entire absence of coliform bacteria during storage; however, few numbers of yeasts were detected in the control yoghurt. On the other hand, the total count of bacteria in control yoghurt was 3.3 x 10 4 c.f.u/ml at day 1 increased in carrot yoghurt samples to the range 3.5 x 10 4 - 4 x 10 4 c.f.u/ml. Also lactic acid bacteria increased in all yoghurt samples. The sensory evaluation indicated acceptance of all yoghurt samples, with preference to the yoghurt prepared using 5% carrot juice, especially in its colour, texture and flavour.